2018
DOI: 10.1038/s41467-018-05000-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymers with on-demand sequence structures via dually switchable and interconvertible polymerizations

Abstract: The synthesis of polymers with on-demand sequence structures is very important not only for academic researchers but also for industry. However, despite the existing polymerization techniques, it is still difficult to achieve copolymer chains with on-demand sequence structures. Here we report a dually switchable and controlled interconvertible polymerization system; in this system, two distinct orthogonal polymerizations can be selectively switched ON/OFF independent of each other and they can be interconverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 62 publications
0
50
0
Order By: Relevance
“…It is reported that the ring-opening product of thiirane could easily insert into C–S bond in C(=S)–S containing molecules, such as trithiocarbonate, or dithiocarbonyl compounds 44 , 46 , 48 . Rhodanine has the highly polarized C=S and weak C–S in the ring, and hence, anion could attack C=S bond easily.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the ring-opening product of thiirane could easily insert into C–S bond in C(=S)–S containing molecules, such as trithiocarbonate, or dithiocarbonyl compounds 44 , 46 , 48 . Rhodanine has the highly polarized C=S and weak C–S in the ring, and hence, anion could attack C=S bond easily.…”
Section: Resultsmentioning
confidence: 99%
“…The conversions of MMA and MRDA both reached~99% to produce copolymer 1 with~10 rhodanine rings per chain. Then excess AIBN was added to remove the trithiocarbonate end groups, preventing it from interfering in following ring-opening polymerization 44 (Supplementary Fig. 46).…”
Section: Knoevenagel Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyer et al [3] reported photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization using Ir(ppy) 3 as a photocatalyst, which can be performed even in the presence of air. In addition, as a useful tool, this technique played an important role in the synthesis of multi-block copolymers [4,5], various stereopolymers [6], copolymers with well-defined sequence structures and sophisticated microstructures [7], and discrete oligomers [8]. Hawker et al reported that Ir(ppy) 3 could be utilized in visible light-induced atom transfer radical polymerization of methacrylates [9], acrylates [10], and to fabricate a 3D polymer brush [11].…”
Section: Introductionmentioning
confidence: 99%
“…Removing the main source of chain-length dependent optical properties, which is a particularity of conjugated polymers doped with a minority fraction of acceptors, requires to ensure all chains carry at least one acceptor, or ideally that the acceptor positioning within the chain is wellcontrolled. Sequence-controlled polymerisation methods have seen a surge in development in the past year for non-semiconducting polymers [60,61,62,63,64], yet these methods remain to be explored to create sequencecontrolled conjugated polymers, where efforts have been limited to the synthesis of well-defined conjugated oligomers [19,18], that are wellbelow the length where the interesting coupling between chain conformation and optical response emerges.…”
Section: Discussionmentioning
confidence: 99%